Self-Formed Quantum Wires and Dots in GaAsP–GaAsP Core–Shell Nanowires - Fonseka, H. Aruni (Nano Lett, 2019)
[Image: see text] Quantum structures designed using nanowires as a basis are excellent candidates to achieve novel design architectures. Here, triplets of quantum wires (QWRs) that form at the core–shell interface of GaAsP–GaAsP nanowires are reported. Their formation, on only three of the six vertices of the hexagonal nanowire, is governed by the three-fold symmetry of the cubic crystal on the (111) plane. In twinned nanowires, the QWRs are segmented, to alternating vertices, forming quantum dots (QDs). Simulations confirm the possibility of QWR and QD-like behavior from the respective regions. Optical measurements confirm the presence of two different types of quantum emitters in the twinned individual nanowires. The possibility to control the relative formation of QWRs or QDs, and resulting emission wavelengths of the QDs, by controlling the twinning of the nanowire core, opens up new possibilities for designing nanowire devices.